Obstacles Facing Inclusive Education in Kindergartens in Karak Governorate - Yahya Husain Othman Al-Qatawneh (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: This study aims to identify the obstacles facing inclusive education in inclusive kindergartens from the point of view of teachers and parents in Karak Governorate. Methods: The study followed an analytical descriptive method. The sample was (100) teachers and parents (60 teachers and 40 parents). The study tool was a scale to measure the obstacles facing inclusion. The number of items on the scale was 65 items distributed over five domains. Results: The results `of the study showed that the obstacles to inclusive learning from the teachers' point of view came to a medium degree. Obstacles to integrating education from the parents' point of view also came to a medium degree in the general average. Conclusions:  The study recommends encouraging families of children with disabilities to educate their children on inclusive education institutions. It also recommends urging authorities responsible for kindergartens to increase their interest in these institutions, through direct follow-up and supervision of the quality of the rehabilitation services provided and the various environmental equipment. The study also recommends activating the channels of communication between kindergarten administration and various civil society institutions.